Non‐destructive depth analysis of the surface oxide layer on Mg2Si with XPS and XAS. (22nd January 2016) - Esaka, Fumitaka; Nojima, Takehiro; Udono, Haruhiko; Magara, Masaaki; Yamamoto, Hiroyuki
Abstract : Depth analysis of the surface oxide layer on a Mg2 Si crystal was performed with X‐ray photoelectron spectroscopy (XPS) and X‐ray absorption spectroscopy (XAS). In XPS, X‐rays from synchrotron radiation with the energies between 2100 and 3300 eV were used as the excitation sources for depth analysis. The Si 1s and Mg 1s XPS spectra show the formation of a thinner SiO2‐X layer at outermost surface and a thicker MgO layer at lower surface on the Mg2 Si. In XAS, total electron yield and partial electron yield (PEY) acquisition modes were used for the measurement of Si K‐edge. The PEY spectrum was obtained by detecting electrons with a fixed kinetic energy of 5, 10, 20, 30, 40, or 50 eV. Although the PEY spectrum with electrons of 5 eV shows similar features with the total electron yield spectrum, detection of electrons with 50 eV gives an increase in the ratio of a peak at 1843.7 eV to the peak assigned to Mg2 Si. The peak at 1843.7 eV can be assigned to the formation of SiO2‐X on the Mg2 Si. From XPS and XAS results, it is indicated that a thinner SiO2‐X layer at outermost surface and a thicker MgO layer at lower surface are formed at initial oxidation of the Mg2 Si. Copyright © 2016 John Wiley & Sons, Ltd.